(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s ((3GHh GdMSf Ydi Hf GHQGgje Hf CMeO Hf jhSa GdJHQjRi s)
(3ChdgG (B:s
(3jHOC HcJGH GdSGde ef GdGSeGA GdKdGKjI GdUMjMI s
(3BNQgG (B:s
(3jfJgi HcJGH GdgeRI Gi GdegehR ef GdGSeGA s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B774s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs